Professor Neena Gupta, Infosys Prize Laureate for Cracking the Zariski Code, One of Math’s Long-Lasting Problems: A Bio-Bibliographic Exploration - Koley, Susanta; Goswami, Sutapa (Information Research Communications, 2026)
Aim Dr. Neena Gupta, a prominent figure in 2024 often called the "Queen of Algebra," has authored 46 research papers between 2011 and 2025. This study presents a bibliometric analysis to provide a quantitative overview and construct her scientific profile. Background For over six decades, the "Zariski Cancellation Problem (1949)" remained unsolved until Dr. Gupta achieved a major breakthrough in 2014 by solving a version in positive characteristic. She was honored with the Infosys Prize in Mathematical Sciences in 2024. Methodology This study analyzes 46 publications from 2011 to 2025 using data from ResearchGate, Google Scholar, and her official website. Standard bibliometric methods were applied to examine research output. Results Dr. Gupta has published 46 papers (11 single-authored, 8 as first author). Peak productivity occurred in 2023 and 2024. Key indicators include: DC (0.76), CC (0.43), CI (2.11), and MCC (0.44). Her most cited 2014 paper has 97 citations. Conclusion Dr. Gupta is a leading figure in modern mathematics whose impactful publications and prestigious honors inspire future generations, especially women in STEM.
Keywords: Affine Algebraic Geometry; Bethune College Kolkata; Calcutta University; Commutative Algebra; Indian Mathematician; Infosys Prize Laurate; ISI Kolkata; Neena Gupta; Oscar Zariski; TIFR Mumbai; Woman Mathematician; Zariski Cancellation Problem; Zariski Code.